Socioeconomic Influence on Caries Susceptibility in Juvenile Individuals with Limited Dental Care: Example from an Early Middle Age Population (Great Moravia, 9th-10th Centuries A.D., Czech Republic) - Gonzalez-Garcin, Virginie; Soulard, Gaëlle; Velemínský, Petr; Stránská, Petra; Bruzek, Jaroslav (IntechOpen, 2012)
None